2018
DOI: 10.1093/jme/tjy102
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Aedes albopictus (Diptera: Culicidae) in the Florida Keys, 2001–2017

Abstract: The presence of Aedes albopictus (Skuse) was first reported in the Florida Keys in 1993. Despite extensive surveillance, the Florida Keys Mosquito Control District (FKMCD) only collected specimens occasionally on a few islands, some years finding no evidence of the invasive species. In 2013-2017, FKMCD witnessed a sudden increase in population size and geographic extent of Ae. albopictus. Samples of Ae. albopictus have now been identified on 30 different islands in the Florida Keys. Three islands in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Additionally, Ae. albopictus has been documented in the Florida Keys, a region where it was previously detected only sporadically (Murray et al 2018). Due to the medical significance of these species and their proximity to humans, it is important for Florida mosquito control programs to regularly survey and document the distribution of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Ae. albopictus has been documented in the Florida Keys, a region where it was previously detected only sporadically (Murray et al 2018). Due to the medical significance of these species and their proximity to humans, it is important for Florida mosquito control programs to regularly survey and document the distribution of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…ABC traps baited with carbon dioxide have been used in all of the surveillance studies conducted by FKMCD. These collections have resulted in new distribution records or confirmation of old collection records for Aedeomyia squamipennis (Lynch Arribalzaga), Aedes albopictus Skuse, Aedes bahamensis Berlin, Aedes condolescens Dyar and Knab, Aedes pertinax Grabham, Aedes scapularis Rondani, Anopheles albimanus Wiedemann, Anopheles grabhamii (Theobald), Psorophora johnstonii (Grabham), Culex coronator Dyar and Knab, Culex declarator Dyar and Knab, Culex peccator Dyar and Knab, Culex tarsalis Coquillett, and Culiseta inornata (Williston) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Adult Surveillancementioning
confidence: 99%
“…Knowledge of blood meal preferences in these areas led to a better understanding of the ecological factors influencing dengue transmission in the Keys [ 79 ]. Murray et al [ 36 ] also reported the use of BG Sentinel traps in collections of the invasive mosquito, A. albopictus , which prior to 1993 had not been seen in the Florida Keys.…”
Section: Adult Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…Aedes aegypti (L.) is the most important mosquitoborne disease vector in south Florida with the capacity to transmit dengue, Zika, and chikungunya viruses (Grubaugh et al 2017, Leta et al 2018, Murray et al 2018, Wilke et al 2019. Aedes aegypti larvae inhabit a variety of domestic containers, and adult females feed predominantly on humans (Hribar and Whiteside 2010;Hribar et al 2001Hribar et al , 2004Pruszynski et al 2020).…”
Section: Introductionmentioning
confidence: 99%